PENGARUH PROFITABILITAS PERUSAHAAN, UKURAN PERUSAHAAN DAN UMUR PERUSAHAAN TERHADAP AUDIT DELAY - Sudarmadi, Sudarmadi; Syamsuri, Syamsuri (Journal of Information System, Applied, Management, Accounting and Research, 2024)
In explaining the supervisory function of the company's performance, shareholders use various measuring instruments to determine the implementation of management's responsibilities to the company, one of the instruments used is the financial statements that have been audited by an independent auditor as an effort to obtain information and financial performance objectively and can be used as a reference. the basis for strategic policy-making, especially companies listed on the company stock exchange that are always noticed by the public. However, the implementation of the audit by the auditor is also determined by the size of the company, thus enabling the auditor to carry out the audit process until the audited financial statements are published without having to experience delays. This study aims to determine: (1) The Effect of Company Profitability on Audit Delay, (2) Effect of Company Size on Audit Delay, (3) Effect of Company Age on Audit Delay, (4) Effect of Company Profitability, Company Size and Company Age on Audit Delay empirical studies on companies listed on the Indonesia Stock Exchange (IDX) with an observation period of 5 (five) years of observation from trading companies listed on the IDX in 2015-2019. Based on the results of this study indicate that company profitability does not affect audit delay, company size does not affect audit delay, company age affects audit delay, and simultaneously company profitability, company size and company age affect audit delay.